Study of the influence of the mortar fine recycled aggregate ratio and the mixing sequence on the behavior of new mortars - Silva Neto, Gilberto Alves da; Leite, Mônica Batista (Ambiente Construído, 2018)
The objective of this study was to investigate the behavior of mortars by replacing a natural fine aggregate (NFA) with mortar fine recycled aggregate (MFRA), with dimensions of less than 2.4mm. In addition, the influence of the mixing sequence over the performance of these mortars was analyzed. For this purpose, the replacement contents, by weight, of 20% and 40%, and two mixing sequences were adopted: the sequence of the Brazilian Standard, NBR 7215 (ABNT, 1996) and an adaptation for mortars (MDE, in Portuguese, Mistura em Duas Etapas) of the Two-Stage Mixing Approach (TSMA), proposed by Tam, Gao and Tam (2005) for recycled concrete. The mortars were produced with cement CPV-ARI, using a mixing proportion of 1.0:5.0 (cement:aggregate, by weight) and a constant water/cement rate of 0.88. To analyze the behavior of the recycled mortars, they were tested in the fresh state and in the hardened state. The study concluded that the partial replacement of the NFA with the MFRA improved some properties of the recycled mortars: the air entrained content and the water absorption rate by capillarity decreased, and the mechanical performance increased. Regarding the influence of the mixing sequence, the adoption of the MDE promoted a better behavior on the mortar properties evaluated.